Trade measures and adjustment of the balance of payments : an analysis of measures and their effects - Organisation for Economic Co-operation and Development (Paris, 1971)
This study deals with the main types of trade measures: quantitative restrictions, custom duties, import surcharges, import deposits, export subsidies, and facilities in the form of export credits and credit guarantees; and with measures affecting imports and exports simultaneously.
Includes bibliographical references.
osc 08/06/2018
Loans
Keywords: Commercial policy; Balance of payments